SCR of NO with C3H6 in the presence of excess O2 over Cu/Ag/CeO2-ZrO2 catalyst - Saidina Amin, Nor Aishah; Chong, C. M. (Elsevier, 2005)

(untitled)
The catalytic activity of a series of CeO2-ZrO2 mixed oxides in the selective catalytic reduction (SCR) of NO by C3H6 at 400'C has been investigated. The NO reduction activity of pure CeO2 is enhanced in the presence of Zr, reaching a maximum NO conversion with CeO2(75)-ZrO2(25) catalyst. Then, the catalytic performances of Cu(4)/Ag(1)/CeO2 and Cu(4)/Ag(1)/CeO2(75)-ZrO2(25) catalysts were compared and the latter showed better activity especially in the low temperature region (250-350 C). The stronger metal-support interaction and higher reducibility shown by the Cu(4)/Ag(1)/CeO2(75)-ZrO2(25) catalyst were believed to enhance its performance compared to Cu(4)/Ag(1)/CeO2 catalyst by activating more C3H6 to selectively reduce NO within this temperature region. Central composite response surface design methodology was employed to study the effect of operating variables such as temperature, NO and C3H6 concentrations on the SCR of NO by C3H6 over Cu(4)/Ag(1)/CeO2(75)-ZrO2(25) catalyst and to determine the optimum value of operating variables for maximum NO conversion. Numerical results indicated that the optimum NO conversion of 82.89% is attained at reaction temperature =415.38 C, NO concentration= 1827.16 ppm and C3H6 concentration = 1908.13 ppm. The addition of water vapor to the reactant significantly decreased the NO conversion over Cu(4)/Ag(1)/CeO2 and Cu(4)/Ag(1)/CeO2 (75)-ZrO2(25), but the inhibition was more pronounced over Cu(4)/Ag(1)/CeO2 catalyst.